Assessment of Cochlear Function during Cochlear Implantation by Extra- and Intracochlear Electrocochleography - Dalbert, Adrian; Pfiffner, Flurin; Hoesli, Marco; Koka, Kanthaiah; Veraguth, Dorothe; Roosli, Christof; Huber, Alexander (Frontiers in Neuroscience, 2018)
Objective: The aims of this study were: (1) To investigate the correlation between electrophysiological changes during cochlear implantation and postoperative hearing loss, and (2) to detect the time points that electrophysiological changes occur during cochlear implantation. Material and Methods: Extra- and intracochlear electrocochleography (ECoG) were used to detect electrophysiological changes during cochlear implantation. Extracochlear ECoG recordings were conducted through a needle electrode placed on the promontory; for intracochlear ECoG recordings, the most apical contact of the cochlear implant (CI) electrode itself was used as the recording electrode. Tone bursts at 250, 500, 750, and 1000 Hz were used as low-frequency acoustic stimuli and clicks as high-frequency acoustic stimuli. Changes of extracochlear ECoG recordings after full insertion of the CI electrode were correlated with pure-tone audiometric findings 4 weeks after surgery. Results: Changes in extracochlear ECoG recordings correlated with postoperative hearing change (r = −0.44, p = 0.055, n = 20). Mean hearing loss in subjects without decrease or loss of extracochlear ECoG signals was 12 dB, compared to a mean hearing loss of 22 dB in subjects with a detectable decrease or a loss of ECoG signals (p = 0.0058, n = 51). In extracochlear ECoG recordings, a mean increase of the ECoG signal of 4.4 dB occurred after opening the cochlea. If a decrease of ECoG signals occurred during insertion of the CI electrode, the decrease was detectable during the second half of the insertion. Conclusion: ECoG recordings allow detection of electrophysiological changes in the cochlea during cochlear implantation. Decrease of extracochlear ECoG recordings during surgery has a significant correlation with hearing loss 4 weeks after surgery. Trauma to cochlear structures seems to occur during the final phase of the CI electrode insertion. Baseline recordings for extracochlear ECoG recordings should be conducted after opening the cochlea. ECoG responses can be recorded from an intracochlear site using the CI electrode as recording electrode. This technique may prove useful for monitoring cochlear trauma intraoperatively in the future.